(untitled) (Social Science Review, 2023)
The One Stop Shop (OSS) is a global concept that accelerates public and private service at the doorstep of citizens. Developing and developing countries have followed this approach to make public service citizen- cantered, inclusive and participatory. The government of Bangladesh has launched the one-stop-shop approach in the name of the Union Information and Service Center (UISC) as part of a partnership program. Over time, the number of one-stop shops has grown at Union, Paurashava and City Corporation level in Bangladesh. The objective of the study is to understand the existing one-stop-shop status in Bangladesh by analysing the role of One Stop Shop in promoting the provision of electronic services at the urban and rural levels. However, the study followed a qualitative design to achieve the goal of the study. Secondary data is collected through content analysis of relevant literature, books, journals and articles, etc. The study finds that there is a manpower (entrepreneurs) shortage and a lack of innovation in services in UDCs, PDCs and CDCs. Bangladesh has not been able to make significant progress and innovations to deliver dynamic public service at urban and rural level through the UDC, PDC and CDC. The study recommends initiating the provision of application-based public and private services through the UDCs, PDCs and CDCs. Social Science Review, Vol. 39(1), June 2022 Page 91-102